2019
DOI: 10.2174/1389450120666190405152315
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Quantum Dots: Promising Theranostic Probes for the Future

Abstract: Nanotechnology has emerged as one of the leading research areas involving nanoscale manipulation of atoms and molecules. During the past decade, the growth of nanotechnology has been one of the most important developments that have taken place in the biomedical field. The new generation nanomaterials like Quantum dots are gaining much importance. Also, there is a growing interest in the development of nano-theranostics platforms in medical diagnostics, biomedical imaging, drug delivery, etc. Quantum dots are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Concern over QD cytotoxicity has been an important research topic over the last few decades, and various methods have been reported to reduce the toxicity of QD during their preparation. Silicon QDs are a family of well-studied QDs owing to their excellent biocompatibility and tunable physical and chemical properties, making them good candidates for theranostic applications (Sivasankarapillai et al 2019). However, when we search through the literature focusing on the cytotoxic properties of all types of QDs, the diverse nature of the individual QD systems makes comparison difficult.…”
Section: Decreasing the Toxicity Of Qds In Biomedical Applicationsmentioning
confidence: 99%
“…Concern over QD cytotoxicity has been an important research topic over the last few decades, and various methods have been reported to reduce the toxicity of QD during their preparation. Silicon QDs are a family of well-studied QDs owing to their excellent biocompatibility and tunable physical and chemical properties, making them good candidates for theranostic applications (Sivasankarapillai et al 2019). However, when we search through the literature focusing on the cytotoxic properties of all types of QDs, the diverse nature of the individual QD systems makes comparison difficult.…”
Section: Decreasing the Toxicity Of Qds In Biomedical Applicationsmentioning
confidence: 99%
“…Thus the antimicrobial and antiviral properties of nanoparticles which are widely reported in scientific literature become a matter of urgent attention in this regard. Many categories of nanomaterials including quantum dots [ 20 ], nanotubes [ 21 ], metal oxide nanoparticles [ 22 ], polymer nanocomposites [ 23 ], two dimensional nanomaterials [ 24 ], lipid nanoparticles [ 25 ] etc, reported for their good antimicrobial activities thus came into the platform of COVID-19 management.…”
Section: Role Of Nanotechnology In the Management Of Viral Diseasesmentioning
confidence: 99%
“…Although inorganic NPs are widely researched in clinical and preclinical settings in the identification, diagnosis, and treatment of various diseases they still raise issues about their effective medical applications regarding factors such as bio-compatibility and specificity. To resolve this, research teams are focusing on inorganic functionalization of the nanoparticles with different kinds of biocompatible constituents thus providing promising benefits of organic as well as inorganic nanoparticles [71]. Gold nanoparticles, being an inorganic nanoparticle offer a great advantage in the treatment of COVID-19.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%